Digital Marketing and Financial Performance of Business Start-Ups in Tuguegarao City: a Basis for Service Learning Program - Catacutan, Karen Joy; Acob, Tisha Marie; Dadap, Johanna Lindsay; Fernandez, Angelina Nicole; Riza Mea, Riza Mea; Moniño, Sara Jane; Noriega, Justyrayra Jerlyn (Journal of Finance and Business Digital, 2024)
This study assessed the influenced of digital marketing strategies on the financial performance of start-ups in Tuguegarao City, addressing a gap in understanding their influence on profitability. Using a descriptive-quantitative research design, data were collected from 35 start-ups and analyzed through descriptive and inferential statistics, specifically Pearson-R for correlation analysis. Findings revealed no significant relationship between digital marketing strategies, such as affiliate marketing, social media marketing, and financial metrics like gross and net profit margins. The conclusion emphasizes that while digital marketing can improve financial outcomes, start-ups should adopt a more tailored approach. The study proposes the seminar "D.I.G.I.T.A.L." to provide these businesses with a deeper understanding of digital marketing strategies for improved performance.